2016
DOI: 10.1007/s10661-016-5433-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pollution of Ganga River water using fish as bioindicator

Abstract: Ganga River, life line of millions of people got heavily polluted due to uncontrolled anthropogenic activities. To monitor the effect of pollution of the river on its aquatic life, a field study was conducted by analyzing the different biomarker enzymes and biochemical parameters in the various tissues (muscles, liver, gills, kidney, brain, and skin) of the Indian major carp Labeo rohita collected from the River Ganga from different study sites of Varanasi district. Activities of antioxidant enzymes, e.g., sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This can be attributed to the alteration in the activity of glucose-6phosphate dehydrogenase and lactate dehydrogenase previously detected by Osman and Harabawy (2010). The concentration of proteins, lipids, and moisture) as well as energy value were found to be significantly lower in the tissues of the river fish due to oxidative stress induced by various contaminants (Vaseem and Banerjee, 2016). The chemical pollutants modulate the metabolism of carbohydrates, causing hyperglycemia by stimulating the glycogenolysis in fish (Lévesque et al, 2002).…”
Section: Discussionmentioning
confidence: 72%
“…This can be attributed to the alteration in the activity of glucose-6phosphate dehydrogenase and lactate dehydrogenase previously detected by Osman and Harabawy (2010). The concentration of proteins, lipids, and moisture) as well as energy value were found to be significantly lower in the tissues of the river fish due to oxidative stress induced by various contaminants (Vaseem and Banerjee, 2016). The chemical pollutants modulate the metabolism of carbohydrates, causing hyperglycemia by stimulating the glycogenolysis in fish (Lévesque et al, 2002).…”
Section: Discussionmentioning
confidence: 72%
“…The study also observed that nitrite pollution increased the accumulation of MDA but it showed the decreasing activity of SOD unlike our result of this experiment. Vaseem and Banerjee [84] found the increased activities SOD, CAT, and increased level of MDA in the fish collected from the heavily polluted river because of uncontrolled anthropogenic activities. They concluded that the result was indicating the pollutant-induced oxidative stress in the fish.…”
Section: Antioxidant Enzyme Activity and Lipid Oxidationmentioning
confidence: 99%
“…High levels of toxicity in fish across almost all waterbodies are a serious concern. Pollution sources include point and non-point agricultural sources (fertilizers and pesticides), sewage (the dominant source of water pollution), solid wastes, domestic wastes, plastics and microplastics, industrial wastes, effluents, oil spills, and in some cases, radioactive wastes (Hameed et al, 1997;Sinha and Khan, 2001;Das, Samanta and Saha, 2007;Gadgil and Heda, 2009;Jha, 2009;Vaseem and Banerjee, 2016;Das, 2018). Fishing nets also contribute to plastic pollution in rivers (Nelms et al, 2021).…”
Section: Water Pollution and Eutrophicationmentioning
confidence: 99%